2019
DOI: 10.1002/ente.201900788
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Sn(II) and Sn(IV) Iodide Perovskites and Study of Their Structural, Chemical, Thermal, Optical, and Electrical Properties

Abstract: Phase‐pure CsSnI3, FASnI3, Cs(PbSn)I3, FA(PbSn)I3 perovskites (FA = formamidinium = HC(NH2)2+) as well as the analogous so‐called vacancy‐ordered double perovskites Cs2SnI6 and FA2SnI6 are mechanochemically synthesized. The addition of SnF2 is found to be crucial for the synthesis of Cs‐containing perovskites but unnecessary for hybrid ones. All compounds show an absorption onset in the near‐infrared (NIR) region, which makes them especially relevant for photovoltaic applications. The addition of Pb(II) and Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 91 publications
(142 reference statements)
4
47
0
Order By: Relevance
“…While most halide perovskites use Pb(II) as unique B‐cation, the partial or total replacement of Pb(II) by Sn(II) has also been investigated by MCS . Saski et al reported pure‐tin mixed‐halide perovskites ASn(Br:I) 3  with good phase purity under inert atmosphere .…”
Section: Mcs As a Way To Investigate Mixed‐composition Halide Perovskmentioning
confidence: 99%
“…While most halide perovskites use Pb(II) as unique B‐cation, the partial or total replacement of Pb(II) by Sn(II) has also been investigated by MCS . Saski et al reported pure‐tin mixed‐halide perovskites ASn(Br:I) 3  with good phase purity under inert atmosphere .…”
Section: Mcs As a Way To Investigate Mixed‐composition Halide Perovskmentioning
confidence: 99%
“…We notice that the 36 h storage of the FASnI 3 film leads to the total degradation of perovskite without SnI 4 or FA 2 SnI 6 characteristic peaks being observed. [ 67,68 ] The improved film stability originates from dense and smooth high‐quality perovskite films with a lower Sn 4+ content with 2,3‐DAPAC treatment, and it is also related to slightly decreased hydrophilicity (Figure S7, Supporting Information). Finally, we compare the PCE and lifetime of our champion PSC with the recently reported passivation works using FASnI 3 as the light absorber.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31–33 ] By the addition of appropriate organic molecules, it is possible to synthesize perovskite nanocrystals. [ 34 ] Furthermore, the mechanochemical synthesis of lead‐free perovskites based on tin, [ 16,35,36 ] copper, [ 37 ] or bismuth [ 38 ] on the B position was demonstrated as well. Mechanochemistry is a solvent‐free synthesis method.…”
Section: Halide Perovskites In Powder Formmentioning
confidence: 99%